Institutional Delivery and Associated Factors in Karnali Province, Nepal - Bhandary , Deepak (Kutumbha vani, 2025)
The area of institutional delivery is the core of the reduction of maternal and neonatal mortality, and the coverage in remote provinces of Nepal is not the same. This study evaluates the institutional delivery determinants in the Karnali Province based on nationally representative data. The data were using Nepal Demographic and Health Survey (NDHS) 2021 Karnali subsample of women who have had a recent live birth (15 49 years). The survey logistic regression was adjusted by age, birth order, education, caste/ethnicity, religion, residence and wealth to institutional delivery (facility vs. home). Sampling weight was used (two strata; 60 PSUs; df=58). The results will be provided as adjusted odds ratios (AOR) with 95 percent confidence intervals (CI). Older maternal age and schooling was positively correlated with institutional delivery, whereas higher parity was negatively correlated with institutional delivery. Age 30 -49 was significantly increased in odds compared to 20 years (AOR = 7.71; 95% CI: 2.1730.38). In comparison with lack of schooling, basic and high education (AOR = 3.23; 1.39-7.50 and 7.31; 2.60- 20.59) augmented utilization. AOR decreased with second (AOR = 0.33; 0.16–0.66) and third/higher births (AOR = 0.25; 0.11-0.55). The odds in the poorer quintile were greater than the poorest (AOR = 2.42; 1.13- 5.22). Religion, caste/ethnicity and rural residence were not big. The model was significant (F (15, 44) =3.41; p=0.0008). Parity, age, economic position, and education determine the facility delivery in Karnali. Girls’ education, transport/financial support and increased facility preparedness are the most critical strategies that should be incorporated to increase safe and respectful childbirth in geographically disadvantaged conditions.